Pengembangan Media Pembelajaran Virtual Reality untuk Meningkatkan Pemahaman Konsep Fisika pada Siswa SMA - Dini Rohmayani; Castaka Agus Sugianto (Journal of New Trends in Sciences, 2024)
The learning of physics, particularly mechanics, poses significant challenges for high school students. Concepts such as Newton’s laws, energy, and three-dimensional vectors are often difficult to grasp using traditional teaching methods. Virtual Reality (VR) has emerged as a promising solution by providing an immersive and interactive learning environment. This study aims to evaluate the effectiveness of VR-based learning media in enhancing students’ understanding of physics concepts, with a specific focus on mechanics. An experimental design was employed, consisting of two groups: an experimental group using VR for learning and a control group receiving traditional instruction. Pre-test and post-test assessments were used to measure the improvement in students' conceptual understanding of physics. The findings indicate that students in the experimental group demonstrated a significant improvement in their understanding of complex physics concepts, such as projectile motion, force, and Newton’s laws, compared to the control group. Students in the experimental group also exhibited higher levels of engagement and motivation, with VR's immersive nature encouraging active participation in learning. The study concludes that VR is an effective tool for enhancing students’ comprehension of abstract and complex physics concepts, improving their visualization and problem-solving skills. Furthermore, VR-based learning provides students with opportunities to conduct virtual experiments and simulations that may not be possible in traditional classroom settings. The implications of this study suggest that VR should be integrated into the physics curriculum to improve learning outcomes, especially in schools with access to the necessary technology. Educators and curriculum developers are encouraged to explore VR’s potential in fostering a more engaging and effective physics education.